Kirkpatrick-Based Evaluation of Agricultural Extension in Black Sapote Gummy Candy Making Training at Karangmojo Fruit Village - Gandis Pramudya Wardani; Epsi Euriga; Adi Prayoga (LP3M IAIFA Kediri, 2026)
The gummy candy training using blacksapote fruit is part of a community empowerment strategy to support the Kampung Buah horticultural program in Karangmojo Hamlet, Sleman. This activity aims to improve the knowledge, attitude, and technical skills of members of the Women's Farmer Group (KWT) Tunas Harapan in processing blacksapote into high-value products. The method used is direct demonstration and hands-on practice, supported by PowerPoint, leaflets, and real materials. Evaluation was conducted using Kirkpatrick’s four-level model and the Wilcoxon Signed Rank Test. The results showed improvements in knowledge (31.2%), attitude (13.9%), and skills (90.5%). The Wilcoxon test revealed a significant difference (p < 0.05) in all aspects. Therefore, this training proved effective in increasing the capacity of female farmers in horticultural product processing and serves as a potential model for local-based community empowerment.